Customer participation in the creation and implementation of the service for internet banking - Ronny . (Universitas Hayam Wuruk Perbanas, 2017)
This study aims to answer two important issues such as what value of internet banking services that is prioritized by the bank in the implementation of internet banking, and how the bank tries to involve the customers in creating and implementing the value of internet banking services. This study conducted by an In-depth interview on 3 informant bank officials from three banks in Indonesia who have authority to handle internet banking services. The analysis was based on the interview result. The results shows that banks expect customers to participate in 5 aspects of internet banking security, feedback in form of input and assessment of internet banking, customer support on the use of adequate technology, customer knowledge and skills about information technology, and customer involvement in new feature development trials of Â Internet banking. Such customer participation leads to service value creation such as security, convenience, benefits, emotional, and communication.